2016
DOI: 10.1038/nn.4458
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy leads to long-lasting changes in human brain structure

Abstract: Pregnancy involves radical hormone surges and biological adaptations. However, the effects of pregnancy on the human brain are virtually unknown. Here we show, using a prospective ('pre'-'post' pregnancy) study involving first-time mothers and fathers and nulliparous control groups, that pregnancy renders substantial changes in brain structure, primarily reductions in gray matter (GM) volume in regions subserving social cognition. The changes were selective for the mothers and highly consistent, correctly clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
565
4
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 587 publications
(614 citation statements)
references
References 68 publications
33
565
4
12
Order By: Relevance
“…As such, it would not be surprising to find that that these circulating fetal progenitor cells would also be able to affect the mother’s central immune system. Also in support of this idea, it is well-known that first-time pregnancy results in significant plasticity within the female brain, both in rodents (Leuner and Sabihi, 2016) and in humans (Hoekzema et al, 2016). In rodents, this plasticity is necessary to induce appropriate postpartum maternal behaviors, and once a dam has given birth for the first time, she is maternal towards any pups she encounters thereafter, even if she is not their biological mother or actively lactating (Bridges, 2015; Fleming et al, 1999).…”
Section: Discussionmentioning
confidence: 70%
“…As such, it would not be surprising to find that that these circulating fetal progenitor cells would also be able to affect the mother’s central immune system. Also in support of this idea, it is well-known that first-time pregnancy results in significant plasticity within the female brain, both in rodents (Leuner and Sabihi, 2016) and in humans (Hoekzema et al, 2016). In rodents, this plasticity is necessary to induce appropriate postpartum maternal behaviors, and once a dam has given birth for the first time, she is maternal towards any pups she encounters thereafter, even if she is not their biological mother or actively lactating (Bridges, 2015; Fleming et al, 1999).…”
Section: Discussionmentioning
confidence: 70%
“…1). A recent longitudinal study of women before pregnancy and at two times points post-pregnancy provided convincing evidence for lasting grey matter volume changes in brain regions involved in social processes 52 . Human motherhood might therefore have a widespread impact on responding to salient emotional information from the environment.…”
Section: Discussionmentioning
confidence: 97%
“…Kim et al (2010) observed increases in grey matter volume when comparing the first to the fourth month postpartum. On the other hand, Hoekzema et al (2017) reported decreases in brain structure (grey matter volume, cortical thickness, surface area) during pregnancy, then minimal changes from 2 months postpartum to 2-year follow-ups. Another paper (Oatridge et al, 2002) reported an overall brain size decrease during pregnancy, but full recovery by six months postpartum.…”
Section: Introductionmentioning
confidence: 93%